2022
DOI: 10.7759/cureus.28341
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Femoral Fractures and Their Surgical Outcomes Between 2011 and 2021: A Single-Centre Observational Study

Abstract: IntroductionPeriprosthetic femoral fractures (PFFs) present a significant burden on the health service. The incidence continues to rise globally as a result of an ageing population and an increase in the number of primary hip and knee arthroplasties being performed. This is a 10-year, retrospective, observational study that aims to better understand the outcomes of PFF in our district general hospital. Materials and methodsWe identified the demographic information of patients who had a PFF and looked at how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Whilst the PPFs are complex cases necessitating thorough planning, delays should be minimised. Baggott et al found longer surgical waiting times in patients who underwent proximal PPF revision rather than proximal PPF fixation [ 15 ]. Part of the surgical delay may be attributable to the fact that successful management of these fractures requires a multi-faceted approach with pre-operative planning, revision templating, and verification of the availability of the required surgical kits.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the PPFs are complex cases necessitating thorough planning, delays should be minimised. Baggott et al found longer surgical waiting times in patients who underwent proximal PPF revision rather than proximal PPF fixation [ 15 ]. Part of the surgical delay may be attributable to the fact that successful management of these fractures requires a multi-faceted approach with pre-operative planning, revision templating, and verification of the availability of the required surgical kits.…”
Section: Discussionmentioning
confidence: 99%